Preconditions of Effective Development of Digital Economy - М. V. Mel’nyk; V. N. Salin (Учёт. Анализ. Аудит)
The objective modern conditions of digital economy include the necessity of the development of innovative sciencebased production, changes in organizational structures based on the integration of business processes of economic entities, the necessity of accelerating business processes and using them as a base for sustainable growth and increased effciency of economic development. Ongoing changes mean the permanent improvement of engineering, technology and organization of production, using big data when making managerial decisions to choose the best developments and practices of solving the tasks on the basis of comparative analysis. It will also help to justify the objective factors in order to realize these decisions and to identify the risky spheres of activity and in turn to choose the effective and feasible directions of development, provide rational for conditions and effectiveness of their implementation in separate economic subjects and the national economy as a whole. The purpose of the article is: to reveal the nature and essence of the digitalization process, its peculiarities in different spheres of economic activity and preconditions of their sustainable development; to identify and highlight the position and the role of digitalization of non-fnancial sector of economy; to systemize the experience useful for implementation of the digitalization project at the modern stage of information technology development; to justify the crucial importance of the development of the system of indicators to fully digitalize the considered modern processes which in turn would require the active development of the system of collection, processing and analysis of the information using information and communication technologies; to draw attention to the topical problem of due staff training both of software developers and IT users; to single out the problems the solution of which can currently determine the prerequisites of success of the “digital economy” project in Russia.